PENGARUH VIRAL MARKETING DALAM TIKTOK TERHADAP MINAT BERKUNJUNG KE ALAM CALDERA KINTAMANI, BALI - Lidya Sari, Marcella; Rena Mariani, Ni Wayan; Ayu Sulasmini, Ni Made (CV. Lafadz Jaya, 2024)
Viral marketing is a marketing strategy that is currently widely used. The existence of social media supports the viral marketing strategy to become a effective marketing strategy for introducing a new product to potential customers. This strategy is said to be effective because at low costs it can reach a wider market. This study aims to examine how viral marketing influences the interest in visiting. The independent variable in this study is viral marketing, and the dependent variable is the interest in visiting. Respondents in this study were TikTok users who had seen content about the Kintamani Bali Caldera Nature. The sample was determined using Slovin's formula with a total of 100 respondents. The data collection technique used a questionnaire. The data analysis techniques in this study include descriptive statistical analysis, simple linear analysis, validity and reliability tests, and hypothesis testing using SPSS version 25. The results of the study show that viral marketing has a positive and significant effect on the interest in visiting, with the T-test result of sig. value 0.003 < 0.05. The coefficient of determination shows 84%, meaning that the influence of viral marketing on the interest in visiting is 84%.